Isolated Scaphoid Dislocation: A Case-Report - Serrano, Sara Dadona Correia; Rezende, Luis Guilherme Rosifini Alves (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Isolated dislocations of the scaphoid are rare conditions in orthopedic practice and can be underdiagnosed. Early diagnosis and treatment are established by the current literature. Despite the few case reports described in the literature, treatment standards are still not well established, with different management techniques for this condition. We present the case report of a 31-year-old patient, presenting isolated dislocation of the left scaphoid. He underwent surgical management with closed reduction and percutaneous fixation with Kirschner wires. After removing the wires, the patient underwent physical therapy. His functional outcomes showed good recovery of function and range of motion of the wrist.